Dampak Kepemimpinan Transformasional Terhadap Inovasi Dan Sehatnya Organisasi (Studi Di Desa Kadubeureum Kecamatan Padarincang Kabupaten Serang) - fentifarleni fenti; Syadeli Hanafi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Leadership as a management function is important to achieve organizational goals. This study aims to investigate the impact of the Village Head's transformational leadership on innovation and organizational health. Transformational leadership with a form of leadership that involves leaders in inspiring, motivating, and changing their subordinates. Innovation is an important factor in increasing the competitiveness of an organization, while the health of an organization reflects the welfare and sustainability of the organization as a whole. This research identifies the link between transformational leadership and organizational innovation. Transformational leadership has the potential to create an enabling environment for innovation. Transformational leaders who are able to communicate an inspiring vision, provide encouragement and support, and empower their followers, can encourage creative thinking, take risks, and create new solutions. In addition, this research also explores the relationship between transformational leadership and organizational health. The method used in this study is a qualitative method, which is carried out by observation, interviews, and document study. Based on the research results it can be concluded that the importance of developing transformational leadership in organizations and the attention given to aspects of innovation and organizational health as well as providing recommendations for leadership practices that prioritize transformational leadership and integrate innovation strategy and organizational health.